Anti-Depression Medication Taking and Risk of Metabolic Syndrome among US Citizens Aged 60+ years: an Across-sectional Analysis of the NHANES 2007-2008 - Jian Liu; John MacIntyre (Journal of Behavior Therapy And Mental Health, 2016)
Objective: To examine whether having metabolic syndrome (MS) among seniors is associated with using anti-depression medication. Methods: A total of 1366 (617 men and 749 women) individuals aged 60+ years from the NHANES 2007/08 survey who had no reported heart disease and/or cancers but had information on prescribed medications in previous month were included in this analysis. All subjects were categorized into three prescribed drug use status, ie, none (group 1); no anti-depressants (group 2); and with anti-depressants (group 3). MS was defined with the criteria of the ATP III. Results: Over 80% of individuals reported taking prescribed medications with 6% of men and 16% of women respectively having used anti-depressants. About 36% of men and 40% of women respectively were considered to have MS. Results from multiple logistic regression analyses indicated that in comparing to group 1, the odds ratios (95% CI) of MS was 2.73 (1.96, 3.82) for group2 and 2.25 (1.07, 4.69) for group 3, respectively. Both group 2 and 3 had a similar metabolic risk profile, in comparing to group 1, they had higher odds of having diabetes and high level of blood pressures. Conclusion: Seniors with medications are more likely to be with MS, diabetes, and high level blood pressures. However, the observed the cardio-metabolic risk association seems similar between seniors using anti-depressant drugs and using other prescribed medications.
Keywords: NHANES